2013
DOI: 10.1007/s11357-013-9524-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial reversal learning is impaired by age in pet dogs

Abstract: Aged dogs spontaneously develop progressive decline in both cognitive and behavioral function, in addition to neuropathological changes, that collectively parallel several aspects of human aging and Alzheimer's disease progression and likely contribute to the development of canine cognitive dysfunction syndrome. In the current study, ethologically relevant spatial learning, retention, and reversal learning tasks were conducted, with the goal of expanding canine neuropsychological testing to pet dogs. Initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 57 publications
3
46
0
Order By: Relevance
“…In another study with pet dogs, there were no significant effects of age on the learning or retention tasks but older dogs ( ≥ 8 years) were significantly Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/25/15 8:54 AM impaired on the reversal learning task when compared with younger ones ( < 8 years). In addition, trial response latency was significantly increased in aged dogs across both the initial and reversal learning tasks but not on the retention task [110]. It has also been reported that while a decline in cognitive ability in canines may not affect survival of dogs, they may manifest other clinical symptoms including sleeping during the day and being restless at night, decreased interaction, disorientation at home, and anxiety [111].…”
Section: Cognitive Functionmentioning
confidence: 95%
“…In another study with pet dogs, there were no significant effects of age on the learning or retention tasks but older dogs ( ≥ 8 years) were significantly Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/25/15 8:54 AM impaired on the reversal learning task when compared with younger ones ( < 8 years). In addition, trial response latency was significantly increased in aged dogs across both the initial and reversal learning tasks but not on the retention task [110]. It has also been reported that while a decline in cognitive ability in canines may not affect survival of dogs, they may manifest other clinical symptoms including sleeping during the day and being restless at night, decreased interaction, disorientation at home, and anxiety [111].…”
Section: Cognitive Functionmentioning
confidence: 95%
“…Ageing in dogs is associated with the decline of several cognitive domains, such as learning, memory, visuospatial function, executive function, and attention (Folstein et al 1975;Head 2014;Landsberg et al 2012;Mongillo et al 2013;Svicero & Amorim 2017;Wallis et al 2014). The visuo-spatial memory domain is particularly interesting, because its decline precedes the onset of declines in other domains.…”
Section: Introductionmentioning
confidence: 99%
“…The testing assessed attentive and spatial abilities with two protocols already in use in our laboratory and previously proved to be sensitive to cognitive impairment in aged pet dogs. Details of the experimental procedures to assess social attention and spatial learning can be found in our previous studies (Mongillo et al 2010(Mongillo et al , 2013.…”
Section: Cognitive Testsmentioning
confidence: 99%
“…As seen in humans, tasks relying on executive functions are the most age-sensitive in the dog species (Studzinski et al 2006;Tapp et al 2003). For instance, aged dogs show decreased abilities to reverse a previously learned stimulus-reward contingency, as shown both in a laboratory canine model of human aging (Studzinski et al 2006) and in healthy aged pet dogs (Mongillo et al 2013). Selective attention is another example of executive function, where a decline has been observed in both aged laboratory Beagle dogs (Snigdha et al 2012) and aged healthy pet dogs (Mongillo et al 2010;Wallis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation